2018
DOI: 10.1016/j.jagp.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Interdisciplinary Model for Evaluation and Treatment of Neuropsychiatric Symptoms: A Cluster Randomized Controlled Trial

Abstract: The implementation of TIME resulted in a significant reduction of agitation among nursing homes patients with dementia. These results should inform training programs for care staff in Norway and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…To have a common QoL measure for all the participants of the present study, we chose the QUA-LID scale to assess QoL including people with mild to severe stages of dementia in the nursing home. This is in line with previous studies using QUALID scale for the assessment of QoL of PWD in the nursing homes and in geriatric psychiatric units [6,51,53]. Since QUALID is a proxy-rated scale, we may have lost valuable information on QoL perceived by people with mild to moderate dementia.…”
Section: Limitations and Strengthssupporting
confidence: 85%
See 1 more Smart Citation
“…To have a common QoL measure for all the participants of the present study, we chose the QUA-LID scale to assess QoL including people with mild to severe stages of dementia in the nursing home. This is in line with previous studies using QUALID scale for the assessment of QoL of PWD in the nursing homes and in geriatric psychiatric units [6,51,53]. Since QUALID is a proxy-rated scale, we may have lost valuable information on QoL perceived by people with mild to moderate dementia.…”
Section: Limitations and Strengthssupporting
confidence: 85%
“…NPS such as delusion, hallucination, and agitation among PWD are often treated with antipsychotics, even though the evidence for a positive effect is uncertain or limited [48,49], with severe side-effects. To enhance the QoL of PWD, adequate management of agitation and other NPS by non-pharmacological interventions-such as TIME (Targeted Interdisciplinary Model for Evaluation and Treatment of NPS) and PCC (Person-centered care) based interventions may-play an important role [50][51][52]. It must be noted that the association between the use of antipsychotics and poorer QoL was not significant in the adjusted linear mixed model in the present study.…”
Section: Resultscontrasting
confidence: 55%
“…encouraging reflective practice, co-creation of SMART action plans, training champions, and offering follow-up supervision and support. Three studies 10,12,13 have reported clinically significant reductions in agitation in care homes. These interventions were intensive and multicomponent, combining the following elements: staff training; increased social interaction; antipsychotic review; physician review of medical history and medications; assessment of pain; a doctor and nurse-led reflective case conference develop ing individualised treatment plans; a 3 h educational lecture; staff role play; 45 min sessions of activity therapy for residents delivered twice a week; and training of care home staff by a doctor and nurse in two 4 h blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Activities in care homes are not necessarily attended by individuals with agitation. 6,9,10 Intensive multicomponent interventions in which physical, social, or occupational activities are implemented, and staff are trained to ensure people with dementia and agitation participate, had some success in reducing agitation in care home residents with dementia immediately after the intervention, [10][11][12][13] with a similar magnitude of effect to antipsychotic medication, but without the associated sideeffects. 14,15 However, such interventions might not be scalable or cost-effective, since they require specialist professional training of care home staff, ongoing supervision to deliver person-centred care and improve communication, physical problems to be addressed, and the implementation of social or other activities, such as positive sensory experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Another 13 studies were excluded, because in closer reading they did not fulfil all of our inclusion criteria. Eventually 7 intervention studies, all of which were RCT's, could be included supplemental to the purpose of our original literature review [66][67][68][69][70][71][72]. Results of these studies affirmed our previous review results that a comprehensive, integrated, multidisciplinary approach, combining medical, psychiatric, psychological and nursing interventions show beneficial effects on severe behavioural problems in NH DCD-patients.…”
Section: Strenghts and Limitationsmentioning
confidence: 75%